On the use of biased randomization and simheuristics to solve Vehicle and Arc Routing Problems - Gonzalez-Martin, Sergio; Barrios, Barry B.; Juan, Angel A.; Riera, Daniel (Proceedings - Winter Simulation Conference, 2014)
This paper reviews the main concepts and existing literature related to the use of biased randomization of classical heuristics and the combination of simulation with meta-heuristics (Simheuristics) in order to solve complex combinatorial optimization problems, both of deterministic and stochastic nature, in the popular field of Vehicle and Arc Routing Problems. The paper performs a holistic approach to these concepts, synthesizes several cases of successful application from the existing literature, and proposes a general simulation-based framework for solving richer variants of Vehicle and Arc Routing Problems. Also examples of algorithms based on this framework successfully applied to concrete cases of Vehicle and Arc Routing Problems are presented.